Engineered Newcastle Disease Virus as an Improved Oncolytic Agent Against Hepatocellular Carcinoma - Altomonte, Jennifer (Nature Publishing Group, 2009)
Newcastle disease virus (NDV) is an intrinsically tumor-specific virus, which is currently under investigation as a clinical oncolytic agent. Several clinical trials have reported NDV to be a safe and effective agent for cancer therapy; however, there remains a clear need for improvement in therapeutic outcome. The endogenous NDV fusion (F) protein directs membrane fusion, which is required for virus entry and cell–cell fusion. Here, we report a novel NDV vector harboring an L289A mutation within the F gene, which resulted in enhanced fusion and cytotoxicity of hepatocellular carcinoma (HCC) cells in vitro, as compared with the rNDV/F3aa control virus. In vivo administration of the recombinant vector, termed rNDV/F3aa(L289A), via hepatic arterial infusion in immune-competent Buffalo rats bearing multifocal, orthotopic liver tumors resulted in tumor-specific syncytia formation and necrosis, with no evidence of toxicity to the neighboring hepatic parenchyma. Furthermore, the improved oncolysis conferred by the L289A mutation translated to significantly prolonged survival compared with control NDV. Taken together, rNDV/F(L289A) represents a safe, yet more effective vector than wild-type NDV for the treatment of HCC, making it an ideal candidate for clinical application in HCC patients.